1999
DOI: 10.1016/s0022-5347(05)68938-0
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Mucosa Urethroplasty for the Treatment of Bulbar Urethral Strictures

Abstract: Preliminary results of urethroplasty for bulbar urethral strictures with a dorsal onlay graft of buccal mucosa are excellent. Longer followup is needed to evaluate definitive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 9 publications
2
15
1
Order By: Relevance
“…Since long, genital skin (prepuce or dorsal penile skin) is used 15,16 and more recently, buccal mucosa has been proposed and has become very popular. [17][18][19] With similar follow up and stricture length, the failure rate of preputial skin or buccal mucosa was exactly equal in our series. The failure rate of dorsal penile skin was significantly higher.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since long, genital skin (prepuce or dorsal penile skin) is used 15,16 and more recently, buccal mucosa has been proposed and has become very popular. [17][18][19] With similar follow up and stricture length, the failure rate of preputial skin or buccal mucosa was exactly equal in our series. The failure rate of dorsal penile skin was significantly higher.…”
Section: Discussionsupporting
confidence: 74%
“…2,5 The dorsal placement of the graft has been described by Barbagli et al, 21 and some authors suggest this technique to be superior. 18,22 Our data however, showed equal failure rates for the ventral or dorsal location. There is a difference between the use of the technique in the penile vs the bulbar urethra.…”
Section: Discussioncontrasting
confidence: 46%
“…In other studies, tubularized buccal mucosal grafts produced successful results in 55-60% of reconstruction, urethral strictures in 40-45% and fistula in 6-45% [26][27][28]. Also, Mehrsai et al [7] reported a 76.5% success rate in a buccal mucosal graft urethroplasty after 28 months of follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Over a median (range) follow-up of 34 (8-72) months, 66 (88%) patients with a one-stage reconstruction (14/16 pendulous; 37/41, 90%, bulbar; 15/16 pan-urethral) remained stricture-free. The mean (range) time to recurrence was 9.4 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) months. Of the nine recurrent strictures, six were managed by one-stage optical urethrotomy and three required a repeat urethroplasty.…”
Section: Resultsmentioning
confidence: 99%